Reflections of Ghanaian life and symbolism in appliqué - Haizel, Maureen (2011)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Master of Arts degree in Fine Painting (Painting),